Mythology : the gods, heroes, and monsters of ancient Greece - Evans, Hestia (Cambridge, Mass. : Candlewick Press, 2007)
A heavily illustrated notebook filled with newspaper clippings, letters, and text, compiled by "Lady Hestia Evans" in "1825."
Keywords: Mythology, Greek -- Juvenile literature; Toy and movable books -- Specimens; Mythology, Greek; Toy and movable books